Teachers' Perception on Giving Reinforcement to the Students with Special Needs - Pakpahan, Asina Romauli (Universitas Pendidikan Ganesha, 2022)
This study aimed at describing the teachers' perception about the advantages, disadvantages, difficulties, strategy, and the types of reinforcement used on giving reinforcement to the students with special needs at SLB Negeri 1 Singaraja. The subjects of this research were 4 English teachers at SLB Negeri 1 Singaraja. The data were collected through questionnaire and interview. The result of this research showed that: (1) English teachers at SLB N 1 Singaraja have a very positive perception about the advantages of reinforcement, (2) English teachers at SLB Negeri 1 Singaraja have a positive perception about the difficulties on giving reinforcement to the students with special needs (3) English teachers at SLB Negeri 1 Singaraja have a very positive perception about the types of reinforcement used by English teachers (4). English teachers at SLB Negeri 1 Singaraja have a positive perception about the strategy in giving reinforcement to the students with special needs.